ANALYSIS OF FINANCIAL STATEMENT BY CAEL AND MANAGEMENT FACTORS METHOD (Case Study at La Tansa BMT Gontor on Period October-December 2012) - Syahruddin Syahruddin; Muhammad Qoshid al hadi (Islamic Economics Journal, 2014)
The collapse of several banks at crisis 1997-1998 makes them closed. But those conditions didn’t occur to Islamic banks because Islamic principles had proven to be able to face the recess. Meanwhile, the established banks are not capable yet to reach SMEs. This opportunity encourages the establishment of non-bank Islamic financial institution, such as BaitulMaalwaTamwil (BMT). As the preventive action of crisis 1997-1998, Bank of Indonesia ruled the regulation of the measurement of financial institution health level, as for BMT. This paper aims for analyzing financial report by using CAEL and management factors in measuring financial health level. Based on the good ratio, then as a whole the measurement of health level of BMT La TansaGontor on October – December 2012 is very health from the performance side and management side.